2006 International Conference of the IEEE Engineering in Medicine and Biology Society 2006
DOI: 10.1109/iembs.2006.260546
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Finger Flexion and Activity Trends over a 25 Hour Period using a Low Cost Wireless Device

Abstract: The goal of this research was to evaluate the usefulness of a wireless custom monitor in measuring real-time finger posture over an extended period of time as the wearer goes about daily life activities. One individual wore the device for 25 continuous hours in the research facility and at home. Initial data analysis methods have been presented to explore different aspects of hand activity over time. Evaluating mean flexion over five minute intervals reveals common hand postures assumed throughout the day, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…This is the first study to quantify characteristics of thumb and finger movement over an extended period of time in people with stroke compared to able-bodied people. Although wearable sensors have been used in stroke rehabilitation to encourage overall upper limb movement [35], previous studies that specifically examined digit movement only reported flexion at a single digit joint [25]. This study adds new information by measuring digit movement using state-of-the-art technology, and quantifying different aspects of digit movement (amplitude, cadence, velocity, idle time) in a similar vein to studies investigating complex movements such as gait.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This is the first study to quantify characteristics of thumb and finger movement over an extended period of time in people with stroke compared to able-bodied people. Although wearable sensors have been used in stroke rehabilitation to encourage overall upper limb movement [35], previous studies that specifically examined digit movement only reported flexion at a single digit joint [25]. This study adds new information by measuring digit movement using state-of-the-art technology, and quantifying different aspects of digit movement (amplitude, cadence, velocity, idle time) in a similar vein to studies investigating complex movements such as gait.…”
Section: Discussionmentioning
confidence: 96%
“…A number of small, proof-of-concept studies have been conducted to develop and validate these methods. In one study, stretch sensors over the metacarpophalangeal joints of the four fingers were worn by an able-bodied subject for 25 hours [25]. Investigators found that the fingers were relatively more extended when performing office work [mean (SD): 19° (10°)] and more flexed when performing self-care and household activities [28° (13°)].…”
Section: Introductionmentioning
confidence: 99%